A conductive hydrogel capable of releasing hydrogen sulfide and its preparation method and application

By developing a conductive hydrogel that can release hydrogen sulfide and combining nanocellulose-modified conductive nanomaterials, the problems of myocardial injury repair and cardiac function recovery are solved, and effective repair of myocardial infarction areas and long-term stable improvement of cardiac function are achieved.

CN117843870BActive Publication Date: 2025-04-11ZHEJIANG UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410023254.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-08
Publication Date
2025-04-11
Estimated Expiration
2044-01-08

AI Technical Summary

Technical Problem

The prior art is difficult to effectively repair damaged myocardium, induce myocardial tissue regeneration, inhibit or reverse poor cardiac remodeling, and there are donor shortages and complications in cardiac transplantation and left ventricular assist devices.

Method used

A conductive hydrogel that can release hydrogen sulfide is developed. By implanting the hydrogel on myocardial tissue, hydrogen sulfide is released to alleviate myocardial ischemia and hypoxia and reduce ROS damage. At the same time, nanocellulose modified conductive nanomaterials promote electrical pulse conduction in the myocardial infarction area, reconstructing synchronous contraction and diastolic of the heart.

Benefits of technology

This hydrogel can effectively improve the adverse microenvironment in the myocardial infarction area, promote the repair and regeneration of myocardial tissue, improve the recovery effect of heart function, and also have good mechanical strength to adapt to dynamic cardiovascular state.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117843870B_ABST
    Figure CN117843870B_ABST
Patent Text Reader

Abstract

The present invention discloses a conductive hydrogel capable of releasing hydrogen sulfide, and a preparation method and application thereof, comprising a hydrogel matrix, a nanocellulose modified conductive nanomaterial, and a hydrogen sulfide donor grafted oxidized polysaccharide, wherein in the hydrogel matrix, polymer molecular chains are entangled to form a three-dimensional network structure, and the nanocellulose modified conductive nanomaterial is uniformly dispersed in the three-dimensional network structure, and establishes strong covalent / or non-covalent interactions with the polymer molecular chains; wherein the mass ratio of the hydrogel matrix, the hydrogen sulfide donor grafted oxidized polysaccharide, and the nanocellulose modified conductive nanomaterial is 1:(0.1-0.5):(0.01-0.02). The present invention improves the strength of the hydrogel by adding the nanocellulose modified conductive material, while ensuring a low loss of elongation at break; and can release hydrogen sulfide gas under the stimulation of cysteine ​​to treat myocardial infarction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of biomedical hydrogels, and in particular relates to a conductive hydrogel capable of releasing hydrogen sulfide, and a preparation method and application thereof. Background Art

[0002] Myocardial infarction is one of the leading causes of death and morbidity worldwide. It is caused by blood clots blocking arteries and eventually leading to heart failure. After myocardial infarction, the highly ordered myocardium is occupied by relatively disordered fibrotic tissue, which loses its original elasticity, leading to abnormal myocardial contraction and relaxation, degenerative ventricular remodeling, decreased myocardial pumping function, and ultimately heart failure.

[0003] Current treatment methods are mainly divided into drug therapy and non-drug therapy. Drug therapy can effectively improve myocardial contractility and reduce cardiac load, but it cannot curb the continuous decline of left ventricular function. Long-term use will cause drug side effects and have limited efficacy. Non-drug therapy mainly includes heart transplantation and left ventricular assist device (LVADS). However, both treatment methods are restricted by a long-term shortage of donors and a series of complications such as thrombosis, infection and stroke.

[0004] Therefore, there is an urgent need to develop new solutions to repair damaged myocardium, induce myocardial tissue regeneration, inhibit or reverse adverse cardiac remodeling, and ultimately achieve long-term stability and improvement of cardiac function. Hydrogels have been proven to be a feasible method for repairing damaged hearts through minimally invasive drug delivery, and are expected to help achieve the goal of therapeutic cardiac regeneration. At the same time, hydrogels can be combined with other active therapeutic drugs to improve their therapeutic efficiency, and have application prospects in the biomedical field. Hydrogen sulfide (H 2 As a gaseous transmitter, H can diffuse rapidly across cell membranes and transmit signals between cells without any mechanism of reuptake or degradation. 2 S can produce a wide range of protective effects, such as anti-inflammatory effects, protection of mitochondrial function, vasodilation, and protection of the cardiovascular system from oxidative stress. At the same time, the conduction of electrical impulse signals between myocardial cells is blocked after myocardial infarction. Conductive hydrogels can reconstruct the synchronous contraction and relaxation of the heart by promoting the conduction of electrical impulses in the myocardial infarction area, which is of great benefit to the recovery of cardiac function. Therefore, an adhesive hydrogel with a certain strength should be developed to adapt to the conditions of moisture and beating of the heart. At the same time, this hydrogel is expected to adhere to the myocardial tissue and stay in the target area for a long time, releasing H2S, thereby improving the reduction of ROS damage, promoting angiogenesis after myocardial infarction, and further promoting cardiac repair. Summary of the invention

[0005] Hydrogel is a feasible method for repairing damaged hearts through minimally invasive drug delivery. The purpose of the present invention is to address the deficiencies of the prior art and provide a conductive hydrogel capable of releasing hydrogen sulfide and a preparation method and application thereof. The hydrogel of the present invention is implanted in myocardial tissue and releases hydrogen sulfide (H 2 S), to relieve the hypoxia in the myocardial ischemic area, and reduce the damage of ROS, which can effectively improve the adverse microenvironment of the myocardial infarction area; at the same time, the hydrogel is loaded with nanocellulose modified conductive nanomaterials with conductive properties to promote the conduction of electrical pulses in the myocardial infarction area to reconstruct the synchronous contraction and relaxation of the heart, and further promote heart repair. The hydrogel has bioadhesion and can be tightly combined with myocardial tissue. At the same time, the nanocellulose modified conductive nanomaterials loaded in the hydrogel provide the hydrogel with good mechanical strength to adapt to the dynamic cardiovascular state.

[0006] The objective of the present invention is achieved through the following technical scheme: a conductive hydrogel capable of releasing hydrogen sulfide, comprising a hydrogel matrix, a nanocellulose-modified conductive nanomaterial and a hydrogen sulfide donor-grafted oxidized polysaccharide, wherein polymer molecular chains are entangled to form a three-dimensional network structure, and the nanocellulose-modified conductive nanomaterial is uniformly dispersed in the three-dimensional network structure to establish strong covalent and / or non-covalent interactions with the polymer molecular chains; wherein the mass ratio of the hydrogel matrix, the hydrogen sulfide donor-grafted oxidized polysaccharide and the nanocellulose-modified conductive nanomaterial is 1:(0.1-0.5):(0.01-0.02).

[0007] Furthermore, the mass ratio of the hydrogel matrix, the hydrogen sulfide donor grafted oxidized polysaccharide and the nanocellulose modified conductive nanomaterial is 1:0.5:0.125.

[0008] The present invention also provides a method for preparing a conductive hydrogel capable of releasing hydrogen sulfide, comprising:

[0009] Adding a conductive nanomaterial dispersion into a nanocellulose suspension to obtain a nanocellulose-modified conductive nanomaterial; the mass ratio of the nanocellulose to the conductive nanomaterial is 1:(0.01-1);

[0010] Dispersing polysaccharide in deionized water, then adding sodium periodate, and obtaining oxidized polysaccharide after reaction; the mass ratio of the polysaccharide to sodium periodate is 1:(0.1-1);

[0011] Adding hydroxylamine-O-sulfonic acid to a potassium hydroxide aqueous solution having a concentration of 0.01 to 0.05 g / mL, and then adding thiobenzoic acid, reacting in an ice bath to obtain a hydrogen sulfide donor SBTHA; the molar ratio of the hydroxylamine-O-sulfonic acid to the thiobenzoic acid is 1:1;

[0012] The oxidized polysaccharide and the hydrogen sulfide donor are added to a mixed solution of dimethyl sulfoxide and water to obtain the hydrogen sulfide donor grafted oxidized polysaccharide after reaction; the mass ratio of the oxidized polysaccharide to the hydrogen sulfide donor is 1:(0.01-0.1); the mass ratio of the dimethyl sulfoxide to the hydrogen sulfide donor is 20:(0.1-0.5);

[0013] A hydrogel matrix, a hydrogen sulfide donor grafted oxidized polysaccharide and a nanocellulose modified conductive nanomaterial are added to deionized water, and then a crosslinking agent is added to form a conductive hydrogel capable of releasing hydrogen sulfide after reaction; the mass ratio of the hydrogel matrix, the hydrogen sulfide donor grafted oxidized polysaccharide and the nanocellulose modified conductive nanomaterial is 1:(0.1-0.5):(0.01-0.02).

[0014] Furthermore, the conductive nanomaterial is selected from one of Mxene, carbon nanotubes, graphene oxide, polyaniline, polypyrrole and polyethylene dioxythiophene; the nanocellulose is selected from one of cellulose nanocrystals, cellulose nanofibers and bacterial cellulose; the diameter of the nanocellulose is 5 to 20 nm and the length is 1 to 3 μm; the polysaccharide is one or more of hyaluronic acid and its derivatives, dextran and its derivatives, water-soluble cellulose derivatives, and sodium alginate; the hydrogel matrix is ​​selected from one or more of hydroxyethyl methacrylate, methacryloylethyl sulfobetaine, carboxylic acid betaine methyl methacrylate, polyvinyl alcohol, and polyacrylic acid; the crosslinking agent is selected from one of methylene bisacrylamide and polyethylene glycol diacrylate.

[0015] Furthermore, the derivatives of hyaluronic acid include oligomeric hyaluronic acid, acetylated sodium hyaluronate, silylated hyaluronic acid and hydroxypropyltrimethylammonium chloride hyaluronic acid, the derivatives of dextran include carboxymethyl dextran and sulfurized esterified dextran, and the water-soluble cellulose derivatives include carboxymethyl cellulose and hydroxyethyl cellulose.

[0016] Furthermore, the mass fraction of the nanocellulose suspension is 0.1% to 1%, and the mass fraction of the conductive nanomaterial dispersion is 0.01% to 1%.

[0017] Furthermore, the mass fraction of the nanocellulose suspension is 0.2-0.5%; the mass fraction of the conductive nanomaterial dispersion is 0.1%-0.5%. In this case, the nanocellulose modified conductive nanomaterial has better dispersibility and is not easy to settle.

[0018] Furthermore, the mass ratio of the nanocellulose to the conductive nanomaterial is 1:(0.02-0.08).

[0019] Furthermore, the mass ratio of the hydrogel matrix, the hydrogen sulfide donor grafted oxidized polysaccharide and the nanocellulose modified conductive nanomaterial is 1:0.5:0.125. The hydrogel made with this ratio has the best mechanical properties, conductive properties and hydrogen sulfide release effect.

[0020] The present invention also provides a use of the conductive hydrogel or the conductive hydrogel prepared by the above preparation method in treating myocardial infarction.

[0021] The beneficial effects of the present invention are:

[0022] (1) The present invention successfully constructed a conductive hydrogel that can release hydrogen sulfide. The strength of the hydrogel was improved by adding nanocellulose to modify the conductive material, while ensuring a low loss of elongation at break;

[0023] (2) The conductive properties in the present invention are provided by the conductive material, and the conductive material is modified by nanocellulose to improve the dispersibility and conductivity of the conductive material;

[0024] (3) The conductive hydrogel constructed by the present invention can release hydrogen sulfide gas under the stimulation of cysteine ​​to treat myocardial infarction. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the accompanying drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings in the following description are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative labor.

[0026] Figure 1 is the Zeta potential diagram of cellulose nanofiber-modified Mxene, where Mxene is a two-dimensional conductive material and CNF is cellulose nanofiber;

[0027] Figure 2 is the NMR image of SBTHA-grafted oxidized dextran, where ODEX is dextran and ODEX-SBTHA is hydrogen sulfide donor-grafted oxidized dextran;

[0028] Figure 3 This is the absorbance graph of SBTHA-grafted oxidized dextran under cysteine ​​stimulation; PBS is phosphate buffer, L-cystenine is L-cysteine, and ODEX-SBTHA is hydrogen sulfide small molecule grafted oxidized dextran;

[0029] Figure 4: is the stress-strain curve of the hydrogel with different contents of nanofiber-modified Mxene; wherein, M represents Mxene, P represents the hydrogel prepared by the present invention, A represents hydroxyethyl methacrylate, S represents methacryloylethyl sulfobetaine, OD represents hydrogen sulfide small molecule grafted oxidized dextran, and the number in front of "MPASOD" represents the mass fraction of nanofiber-modified Mxene in the hydrogel system;

[0030] Figure 5 Electrical conductivity of hydrogels of nanofiber-modified MXene with different contents. DETAILED DESCRIPTION

[0031] The technical solution of the present invention is further described in detail below in conjunction with embodiments, but the protection scope of the present invention is not limited to the following.

[0032] Example 1

[0033] A conductive hydrogel capable of releasing hydrogen sulfide comprises the following steps:

[0034] (1) Preparation of nanocellulose-modified Mxene

[0035] 2 mL of MXene dispersion (1 mg / mL, mass fraction 0.1%) was slowly added dropwise to 2 g of nanocellulose dispersion (specifically cellulose nanofiber CNF, mass fraction 0.5%, diameter distribution 5-20 nm, length distribution 1-3 μm), stirred for reaction for 1 hour, and then ultrasonicated for 15 minutes to obtain a mixed dispersion of nanocellulose and MXene.

[0036] (2) Preparation of oxidized dextran

[0037] 5 g of dextran was dispersed in 250 mL of deionized water, and then 2.5 g of sodium periodate was added, and the mixture was reacted for 24 h in the dark, and then 3 mL of ethylene glycol was added to terminate the reaction. Finally, the resulting mixture was dialyzed and freeze-dried to obtain oxidized dextran.

[0038] (3) Preparation of hydrogen sulfide donor SBTHA

[0039] 1.13 g of hydroxylamine-O-sulfonic acid was added to 30 mL of potassium hydroxide aqueous solution (concentration: 0.04 g / mL), and 1.38 g of thiobenzoic acid was added dropwise in an ice bath. The mixture was reacted for 20 minutes and filtered to obtain white solid SBTHA.

[0040] (4) Preparation of SBTHA-grafted oxidized dextran

[0041] 2 g of the above-prepared oxidized dextran and 20 mg of small hydrogen sulfide molecule (SBTHA) were added to a mixed solution of dimethyl sulfoxide (DMSO) and water, and a catalyst trifluoroacetic acid was added. After reacting for 2 hours under a nitrogen atmosphere, the reaction mixture was precipitated with ethanol to obtain SBTHA-grafted oxidized dextran.

[0042] (5) Preparation of conductive hydrogel

[0043] 3 g HEMA, 1 g SBMA, 0.5 g SBTHA grafted oxidized dextran, and a mixed dispersion of 2 g nanocellulose and MXene were added to 8 g deionized water and stirred for a period of time. Then, the initiator ammonium persulfate (APS) and the cross-linking agent methylenebisacrylamide (MBA) were added, and after a period of reaction, a hydrogel was formed.

[0044] It should be noted that in other embodiments of the present invention, other different schemes obtained by making specific selections within the scope of the steps, components, ratios, and process parameters recorded in the present invention can all achieve the technical effects recorded in the present invention, so the present invention will no longer list them one by one.

[0045] Property monitoring of embodiments

[0046] The following properties of the conductive hydrogel capable of releasing hydrogen sulfide prepared in the above embodiment of the present invention were tested:

[0047] Polyvinyl alcohol (PVA) is a hydrophilic polymer with great potential as a hydrogel matrix in biomedical applications due to its biocompatibility, cohesion, porosity and excellent water adsorption. Two-dimensional MXene nanosheets have abundant functional groups, large lateral size and excellent conductivity, which can establish more efficient conductive pathways. CNF, as a naturally abundant bio-derived nanomaterial, has achieved great success as an interfacial stabilizer in stabilizing discrete nanomaterials or microparticles. In addition to preventing the merging of adjacent nanosheets, the abundant hydroxyl or carboxyl groups on the surface of CNF can also interact positively with the polymer chains of the hydrogel through hydrogen bonds, thereby improving the mechanical properties of the hydrogel.

[0048] Zeta potential diagram of cellulose nanofiber modified Mxene

[0049] Figure 1 is the Zeta potential diagram of cellulose nanofiber modified Mxene, from Figure 1It can be seen that the zeta potential of pure Mxene solution is -11.1mV, while the zeta potential of CNF-stabilized Mxene colloidal solution is -31mV. The reason why CNF and colloidal solution have such high stability may be that the hydroxyl and carboxyl groups on CNF have strong interactions with the groups on the Mxene two-dimensional sheets, so that the CNF layer tightly wraps the Mxene two-dimensional sheets and prevents the aggregation of the Mxene two-dimensional sheets.

[0050] H NMR Spectrum of SBTHA-Grafted Oxidized Dextran

[0051] Depend on Figure 2 It can be seen that ODEX has an additional chemical shift at 4.8-5.4 ppm, indicating that the aldehyde group is converted into hemiacetate, and the ODEX-SBTHA NMR curve finds that the characteristic peak of the benzene ring appears in the range of 8.0-9.0 ppm, which may be that SBTHA is grafted onto the aldehyde group of ODEX.

[0052] Absorbance of SBTHA-grafted oxidized dextran stimulated by cysteine

[0053] In the presence of sulfhydryl-containing amino acids such as glutathione or cysteine, SBTHA-grafted oxidized dextran can release hydrogen sulfide. Figure 3 It can be seen that only when ODEX-SBTHA and cysteine ​​exist at the same time, ODEX-SBTHA will release hydrogen sulfide, thereby changing the absorbance of its solution.

[0054] Stress-strain curves of hydrogels modified with nanofibers of different contents of Mxene

[0055] Figure 4 is the stress-strain curve of the hydrogel with different contents of nanofiber modified Mxene. Figure 1 It can be seen that with the increase of the content of nanofiber-modified Mxene, the tensile strength and elongation at break of the hydrogel both show a trend of first increasing and then decreasing. The gel with a content of 6% has a tensile strength of 190KPa and an elongation at break of 2152%. Even if the content of nanofiber-modified Mxene increases to 10%, the gel still has a tensile strength of 129KPa and an elongation at break of 2109%. This is because the addition of Mxene increases the interaction force between chains in the three-dimensional network of the hydrogel, resulting in an increase in tensile strength and a decrease in elongation at break.

[0056] Conductive properties of hydrogels modified with different contents of nanofibers and Mxene

[0057] Conductivity is a parameter used to describe the ease with which electric charges flow in a substance and is used to evaluate the conductivity of hydrogels. Figure 5 It can be seen that the conductivity of the hydrogel increases rapidly with the increase of the content of nanofiber-modified MXene, and the conductivity of 6% content reaches 164 mS / cm.

[0058] The above is only a preferred embodiment of the present invention. It should be understood that the present invention is not limited to the form disclosed herein, and should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications and replacements, and can be within the scope of the concept described herein. The changes and modifications made by those skilled in the art do not deviate from the spirit and scope of the present invention and should be within the scope of protection of the claims attached to the present invention.

Claims

1. A conductive hydrogel capable of releasing hydrogen sulfide, characterized in that: It includes a hydrogel matrix, nanocellulose modified MXene and hydrogen sulfide donor grafted oxidized dextran, in which polymer molecular chains are entangled to form a three-dimensional network structure, and the nanocellulose modified MXene is uniformly dispersed in the three-dimensional network structure to establish strong covalent / or non-covalent interactions with the polymer molecular chains; wherein the hydrogel matrix is ​​selected from hydroxyethyl methacrylate and methacryloylethyl sulfobetaine; the mass ratio of the hydrogel matrix, hydrogen sulfide donor grafted oxidized dextran, nanocellulose and MXene mixed dispersion is 1:0.125:0.5; the nanocellulose and MXene mixed dispersion is the nanocellulose modified MXene; Among them, the preparation method of the nanocellulose modified MXene mixed dispersion includes: adding 2 mL of MXene dispersion with a concentration of 1 mg / mL and a mass fraction of 0.1% to 2 g of nanocellulose dispersion with a mass fraction of 0.5%, stirring the reaction for 1 hour, and then ultrasonicating for 15 minutes to obtain a nanocellulose and MXene mixed dispersion.

2. A method for preparing a conductive hydrogel capable of releasing hydrogen sulfide, characterized in that: include: Adding the MXene dispersion into the nanocellulose suspension to obtain a mixed dispersion of nanocellulose and MXene, i.e., nanocellulose-modified MXene; the mass ratio of the nanocellulose to the MXene is 1:(0.01-1); Dispersing dextran in deionized water, then adding sodium periodate, and obtaining oxidized dextran after reaction; the mass ratio of the dextran to the sodium periodate is 1:(0.1~1); Adding hydroxylamine-O-sulfonic acid to a potassium hydroxide aqueous solution having a concentration of 0.01-0.05 g / mL, and then adding thiobenzoic acid, and reacting in an ice bath to obtain a hydrogen sulfide donor SBTHA; the molar ratio of the hydroxylamine-O-sulfonic acid to the thiobenzoic acid is 1:1; Adding oxidized dextran and hydrogen sulfide donor into a mixed solution of dimethyl sulfoxide and water, and obtaining hydrogen sulfide donor-grafted oxidized dextran after reaction; the mass ratio of the oxidized dextran to the hydrogen sulfide donor is 1:(0.01-0.1); the mass ratio of the dimethyl sulfoxide to the hydrogen sulfide donor is 20:(0.1-0.5); A hydrogel matrix, hydrogen sulfide donor grafted oxidized dextran and nanocellulose modified MXene are added to deionized water, and then a cross-linking agent is added to form a conductive hydrogel that can release hydrogen sulfide after reaction; the hydrogel matrix is ​​selected from hydroxyethyl methacrylate and methacryloylethyl sulfobetaine; the mass ratio of the hydrogel matrix, hydrogen sulfide donor grafted oxidized dextran and nanocellulose and MXene mixed dispersion is 1:0.125:0.

5.

3. The method for preparing a conductive hydrogel capable of releasing hydrogen sulfide according to claim 2, characterized in that: The nanocellulose is selected from one of cellulose nanocrystals, cellulose nanofibers and bacterial cellulose; the diameter of the nanocellulose is 5-20 nm and the length is 1-3 μm; the cross-linking agent is selected from one of methylene bisacrylamide and polyethylene glycol diacrylate.

4. The method for preparing a conductive hydrogel capable of releasing hydrogen sulfide according to claim 2, characterized in that: The mass fraction of the nanocellulose suspension is 0.1% to 1%, and the mass fraction of the MXene dispersion is 0.01% to 1%.

5. The method for preparing a conductive hydrogel capable of releasing hydrogen sulfide according to claim 4, characterized in that: The mass fraction of the nanocellulose suspension is 0.2-0.5%; the mass fraction of the MXene dispersion is 0.1%-0.5%.

6. The method for preparing a conductive hydrogel capable of releasing hydrogen sulfide according to claim 2, characterized in that: The mass ratio of the nanocellulose to MXene is 1:0.

2.

7. Use of the conductive hydrogel according to claim 1 or the conductive hydrogel prepared by the preparation method according to any one of claims 2 to 6 in preparing a drug for treating myocardial infarction, characterized in that: The conductive hydrogel releases hydrogen sulfide gas under the stimulation of cysteine.

Citation Information

Patent Citations

  • Preparation method of multifunctional conductive composite hydrogel based on nanocellulose

    CN115466408A

  • Controlled chemical release of hydrogen sulfide

    US20130253051A1